The Potential of Brewer’s Spent Grain in the Circular Bioeconomy: State of the Art and Future Perspectives - Zeko-Pivač, Anđela; Tišma, Marina; Žnidaršič-Plazl, Polona; Kulisic, Biljana; Sakellaris, George; Hao, Jian; Planinić, Mirela (Frontiers in Bioengineering and Biotechnology, 2022)
Brewer’s spent grain (BSG) accounts for approximately 85 % of the total mass of solid by-products in the brewing industry and represents an important secondary raw material of future biorefineries. Currently, the main application of BSG is limited to the feed and food industry. There is a strong need to develop sustainable pretreatment and fractionation processes to obtain BSG hydrolysates that enable efficient biotransformation into biofuels, biomaterials, or biochemicals. This paper aims to provide a comprehensive insight into the availability of BSG, chemical properties, and current and potential applications juxtaposed with the existing and emerging markets of the pyramid of bio-based products in the context of sustainable and circular bioeconomy. An economic evaluation of BSG for the production of highly valuable products is presented in the context of sustainable and circular bioeconomy targeting the market of Central and Eastern European countries (BIOEAST region).